Efficiency calibration of a gamma-ray detector for measuring environmental radiation - Bulala, Avuyile Sisanda (University of Cape Town, 2020)
The Environmental Radioactivity Laboratory (ERL) of iThemba LABS conducts research into levels of natural and anthropogenic radioactivity in the environment. The laboratory-based measurements are conducted using a low-background Hyper Pure Germanium (HPGe) detector system. A critical aspect of such measurements involves calibrating the detector about energy and detection efficiency. The present study details experiment that were carried to determine both energy and efficiency calibrations for various sample geometries using gamma-ray spectrometry. The measurements using reference sources of known activity were carried out using two sample holders (Marinelli Beaker (1000 ml) and, a cylindrical pill bottle (100 ml)), and a point source. The IAEA reference materials (RGU-1, RGTh-1 ore and RGK-1) were prepared and used to fill the Marinelli beaker and pill bottles. Certified reference point sources (⁶⁰Co, ¹⁵²Eu, ¹³⁷Cs, ²²Na, ²⁴¹Am and ¹³³Ba) were obtained from the National Metrology Institute of South Africa (NMISA). Experiments consisted of exposing the HPGe detector to various gamma-ray sources prepared using various sample holders and the point source geometry. The counting time for each measurement was 24 hours. Each spectrum was analysed by inserting region of interests around suitably selected photo-peaks and the counts associated with these photo-peaks were automatically determined and corrected for background by the software. The full energy peak detection efficiency was then determined from the background corrected counts, the known activity of the source and the implicit in measurement (solid angle). The experimental and simulated spectra using point sources and volume sources were compared. Both experimental and simulated spectra presented showed a good agreement in terms of shape and varying intensities as expected. Additional photo-peaks were observed from ²²Na, ⁶⁰Co, ¹³³Ba and ¹⁵²Eu (point sources) and ²³²Th and ²³⁸U (volume sources) experimental spectra these effects were not observed in the simulated spectra. These additional peaks observed are the result of coincidence summing in some of gamma emitting radionuclides. Efficiencies that were experimentally determined, were compared with the calculated efficiencies from Monte Carlo simulations using MCNPX. Efficiency calibration parameters (power fit function) for the volume sources were determined from experimental and simulated data; a = 2.58; b = -0.75 experimental and a = 1.01; b = 0.65 simulated (100 mL pill bottle) and a = 2.07; b = -0.75 experimental and a = 1.61; b = 0.66 simulated (1 L Marinelli beaker). The simulated parameters for the efficiency as determined can be used for future calculations of activity concentrations when the 100 mL pill bottle or 1 L Marinelli Beaker sample holder is used. Further improvement in these calculations can be achieved by considering the sample density. The simulation input files used to generate these values is available and can be modified to match any sample holder geometry, as well as any density that might be required in future counting.